On moments of probability distribution functions and H-function transform - Raina, R. K.; Kalla, S. L. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
We express the absolute moments of a probability distribution function in terms of the H-function transform. A special case and an example is cited to illustrate the application of our general result.